Evaluation of Erythrocyte Malondialdehyde, Glutathione Concentration and Serum Nitric Oxide Levels in Patients with Toxoplasma gondii - Al-Azzauy, A. A. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The aim of this study was to evaluate the biological importance of the magnitude of oxidative stress, antioxidant and the levels of nitric oxide (NO) in the female patients infected with Toxoplasma gondii by analyzing the levels of erythrocyte malondialdehyde (MDA) as an indicator for the oxidative stress and erythrocyte reduced glutathione (GSH) level as indicator for the antioxidant status and serum nitric oxide levels. This prospective study was conducted on fifty female patients with toxoplasmosis and thirty normal healthy females of comparable age and sex were considered as normal control. A statistically significant difference was found between patients and control group in terms of MDA, GSH and NO levels. A decrease in erythrocyte GSH levels was detected, while erythrocyte MDA and serum NO levels increased significantly as compared with normal healthy control. Consequently, the results suggest that the high infection vs control of increased erythrocyte MDA and serum NO levels probably suggest the occurrence as a mechanism of tissue change in cases of toxoplasmosis. Moreover, it is recommended that the patient levels of MDA, GSH, and NO should be evaluated in toxoplasmosis.